"I See the Fretboard in Diagrams": An Examination of the Improvisatory Style of Herbert Lawrence "Sonny" Greenwich - Scott, Andrew (Canadian University Music Review / Revue de musique des universités canadiennes, 2003)
In this article, the author examines the improvisatory style of jazz musician Herbert Lawrence "Sonny" Greenwich. While numerous extra-musical sources inform the guitarist's performances, the cubist paintings of Paul Klee are particularly meaningful. Through transcription, analysis and interview, the author demonstrates that fretboard "diagrams"—which Greenwich suggests originate from Klee—act in a threefold manner. First, they afford Greenwich a personal way of discussing his craft, second they offer a formulaic and perceptual strategy for traversing various harmonic terrains and third these diagrams act as a surrogate music theory for the self-taught musician, affording him a unique method of organizing the guitar.